IMPLEMENTATION OF WORDWALL AS A LEARNING MEDIA TO IMPROVE STUDENTS' WRITING SKILL - Faisal, Faisal Amri; Sukmaningrum, Rahmawati (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study examines the effectiveness of Wordwall as a learning media in enhancing the writing skill of students. The Wordwall is an innovative and interactive tool that utilizes technology to engage students in writing activities. A review of related literature suggests that Wordwall as a learning media has been successfully implemented in various contexts to enhance students' writing skill. This study utilized a pre-experimental design known as a one-group pretest-posttest design. This design involved a single group of participants who underwent two measurements: a pretest was conducted prior to the intervention and then followed by a posttest. By comparing the participants' performance on the pretest and posttest, the study aimed to evaluate the impact of the intervention on the measured variable. The results showed that the group taught using Wordwall had a significant improvement in their writing skill. The results of this study have practical implications for language teachers to consider using Wordwall as a learning media to enhance their students' writing skill. Keywords: wordwall as a learning media, writing skill, interactive learning, technology-based learning